2019
DOI: 10.1123/ijspp.2018-0545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric and Directional Training on Physical Fitness Parameters in Youth Soccer Players

Abstract: This study supports that a short-term combined program of PT and COD exercises can improve jumping ability, acceleration, and endurance parameters in youth soccer players. The small training effect could be explained when taking into account the level of the participants, the duration of the program and the low volume of COD exercises that were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
29
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 25 publications
12
29
0
15
Order By: Relevance
“…Makhlouf et al [19] reported that such training enhanced change-of-direction ability (Illinois agility test (ICODT) without a ball and 4 m × 9 m shuttle run test (agility 4 m × 9 m)) in prepubertal male soccer players. Additionally, Michailidis et al [20] noted that such training improved vertical and horizontal jump performance (squat jump and long jump), change-of-direction ability, and sprint performance over 10 m in prepubertal male soccer players. Furthermore, Hammami et al [6] studied the effects of combined plyometric and short sprint with change-of-direction (PSSCoD) training in male U15 handball players.…”
Section: Introductionmentioning
confidence: 99%
“…Makhlouf et al [19] reported that such training enhanced change-of-direction ability (Illinois agility test (ICODT) without a ball and 4 m × 9 m shuttle run test (agility 4 m × 9 m)) in prepubertal male soccer players. Additionally, Michailidis et al [20] noted that such training improved vertical and horizontal jump performance (squat jump and long jump), change-of-direction ability, and sprint performance over 10 m in prepubertal male soccer players. Furthermore, Hammami et al [6] studied the effects of combined plyometric and short sprint with change-of-direction (PSSCoD) training in male U15 handball players.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is based on the principle of training specificity ( Behm and Sale, 1993 ) which implies that training must attempt to closely mimic the demands of the respective sport specific activity ( Behm and Sale, 1993 ). Two recent studies have shown training-related improvements when combining plyometric training with sprint and change of direction with 14–15 years old ( Hammami et al, 2018 ) and 11–12 year old children ( Michailidis et al, 2018 ). The older youth experienced training improvements with 6 of 8 tests, whereas the 12 years old youth only experienced training advantages with 2 of 8 tests.…”
Section: Introductionmentioning
confidence: 99%
“…Long jump is divided into four phases, including prefix, repulsion, drift, and landing (Yadav & Paris, 2014;Michailidis, Tabouris, & Metaxas, 2019). Prefix is the initial movement in the form of running to gain the speed for repulsion or jumping.…”
Section: Introductionmentioning
confidence: 99%